The Effect of Entrepreneurial Factors on the Realization of Sustainable Development Goals (SDG) and Sustainability in Indonesia’s SMEs - Anindia Pratiwi Putri; Wawan Dhewanto (Bina Nusantara University, 2022)
The International Monetary Fund (IMF) predicts Indonesia with lower economic growth than other countries in South Asia. This problem can be addressed by understanding the values ​​of Sustainable Development Goals (SDG) 8 about decent work and economic growth. However, previous research has not identified entrepreneurial factors that drive SDG 8 and how they affect sustainability. The research aimed to analyze the interrelationships of entrepreneurial factors in realizing SDG 8 and sustainability scientifically and systematically to fill the gap. The research applied a quantitative method. Small and Medium-Sized Enterprises (SMEs) in Bandung were selected as the research population using the purposive sampling method. Questionnaires were distributed to 153 SMEs as a data collection method. A seven-point Likert scale was used to measure respondents’ agreement for each item or statement. Then, the data were processed using PLS-SEM. The research finds that entrepreneurial intentions and behavior are entrepreneurial factors with a significant positive effect on SDG 8. In addition, SDG 8 has a significant positive effect on sustainability (social, economic, and environmental). Last, the research also contributes to increasing the entrepreneurs’ awareness in understanding the importance of motivation, entrepreneurial intentions, and SDG 8 to realize sustainable SMEs.